2016
DOI: 10.1007/s10620-016-4203-5
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Gastroenteritis: An Underdiagnosed Condition

Abstract: EOGE is an underdiagnosed condition. In contrast to eosinophilic esophagitis; the disease might be female-predominant in adults. High index of clinical suspicion is required for diagnosis. Further studies about the long-term outcomes and the efficacy of restriction diet in adult patients are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
45
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 30 publications
0
45
0
11
Order By: Relevance
“…In an autopsy study, low-grade eosinophilic infiltration and degranulation in the gut was observed to occur in normal subjects although eosinophil counting (quantitative histology) was not performed [8]. In the present study by Alhmoud et al [1], the limit applied was [25 eosinophils/HPF in the proximal GI tract and 50/HPF in the colon. A similar definition was applied in the more recent Mayo Clinic series with a median count of 82 eosinophils/HPF reported in EG but within a remarkably wide range of 4-300/HPF [4].…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…In an autopsy study, low-grade eosinophilic infiltration and degranulation in the gut was observed to occur in normal subjects although eosinophil counting (quantitative histology) was not performed [8]. In the present study by Alhmoud et al [1], the limit applied was [25 eosinophils/HPF in the proximal GI tract and 50/HPF in the colon. A similar definition was applied in the more recent Mayo Clinic series with a median count of 82 eosinophils/HPF reported in EG but within a remarkably wide range of 4-300/HPF [4].…”
mentioning
confidence: 59%
“…Although Alhmoud et al [1] report eosinophilic colitis is even less common than proximal gut disease, the eosinophil is also important in the colon. Another new distinct colonic EGID has recently been described linked to chronic bacterial infection and the irritable bowel syndrome (IBS) [13].…”
mentioning
confidence: 99%
See 3 more Smart Citations